Adaptive isogeometric analysis–based phase-field modeling of brittle electromechanical fracture in piezoceramics. (15th October 2022) - Kiran, Raj; Nguyen-Thanh, Nhon; Zhou, Kun
Highlights: Adaptive isogeometric formulation based on polynomial splines over hierarchical T-meshes (PHT-splines) is developed to investigate electromechanical fracture in piezoceramics. The evolution of the crack phase-field within the framework of coupled electromechanical constitutive relationships is considered. The approach can efficiently capture complex propagation patterns including deflection and twisting under different complex electromechanical loadings in 2D and 3D cracked piezoceramics. Abstract: The investigation of brittle fracture in piezoceramics under complex electromechanical loading is critical for their durable design and optimal utilization. Phase-field modeling offers a convenient and effective strategy to tackle three-dimensional (3D) fracture problems through the regularization of sharp crack topologies. This paper aims to develop an adaptive phase-field model to study electromechanical fracture in piezoceramics via an isogeometric formulation based on polynomial splines over hierarchical T-meshes (PHT-splines). In particular, we (i) consider the evolution of the crack phase-field within the framework of coupled electromechanical constitutive relationships, (ii) implement PHT-splines to make adaptive refinement computationally efficient and overcome the limitation of nonuniform rational B-splines-based isogeometric formulations, (iii) benchmark our findings with experiments and other numerical studies, and (iv) capture complex crack propagation patterns including deflection and twisting under different complex electromechanical loading conditions in 2D and 3D cracked piezoceramics. The computational efficiency of the implemented phase-field model in cracked piezoceramics is improved through facilitating the adaptive mesh refinement during crack propagation. The proposed scheme lays down the foundation for modelling the diffusive electromechanical fracture in cracked piezoceramics.